مستوى فاعلية نظم المعلومات المحاسبية في المصارف التجارية الليبية دراسة استطلاعية على المصارف الليبية - عماد عبد الله فضل الله (Scientific Journal of University of Benghazi, 2020)
This study aimed to identify and improve the level of effectiveness of accounting information systems in Libyan commercial banks. This system can provide appropriate accounting information for the managements and improve their functions by building significant recommendations. The Libyan commercial banks in the eastern side of Libya were targeted to obtain the data by using a questionnaire form. This form was designed carefully to include significant points according to a typical five-level Likert scale. The descriptive analytical approach was followed in analyzing the data in this study. One of the important findings is that the accounting information system provided significant information which can be used by the Libyan commercial bank management to set future plans and goals. This also can help to set of control indicators that were used by the administration of Libyan commercial banks in detecting deviations, analyzing their causes and treating them. One of important recommendations in this study, is the necessity for the management of Libyan commercial banks to give greater importance and attention to relying on accounting information systems in their operations formed in planning, control and decision-making as well as relying on them to provide the information for estimating the budgets.